2007
DOI: 10.1002/aic.11314
|View full text |Cite
|
Sign up to set email alerts
|

Modeling gas displacement kinetics in coal with Maxwell‐Stefan diffusion theory

Abstract: in Wiley InterScience (www.interscience.wiley.com).The kinetics of binary gas counter-diffusion and Darcy flow in a large coal sample were modeled, and the results compared with data from experimental laboratory investigations. The study aimed for a better understanding of the CO 2 -sequestration enhanced coalbed methane (ECBM) recovery process. The transport model used was based on the bidisperse diffusion mechanism and Maxwell-Stefan (MS) diffusion theory. This provides an alternative approach to simulate mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Maxwell-Stefan diffusion theory [56] is superior for describing diffusion of mixed gases in coals compared with the constant Fick diffusivity model. So far many attempts have been made to model gases diffusion in coals and the results suggested that the diffusion coefficient is strongly dependent on gas species and concentration [11,28,62,65,68].…”
Section: Multicomponent Gas Counter-diffusion In Coal Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…Maxwell-Stefan diffusion theory [56] is superior for describing diffusion of mixed gases in coals compared with the constant Fick diffusivity model. So far many attempts have been made to model gases diffusion in coals and the results suggested that the diffusion coefficient is strongly dependent on gas species and concentration [11,28,62,65,68].…”
Section: Multicomponent Gas Counter-diffusion In Coal Matrixmentioning
confidence: 99%
“…sorption, gas flow, and play important roles for CBM recovery as summarized in Table 2. 2.3 Coupling processes in CBM recovery CBM recovery results from migration of gas in coal, simultaneously dealing with the several coupling processes, i.e. gas sorption, gas diffusion, gas flow and permeability change responded to adsorption/desorption, diffusion and gas flow [28,29], as illustrated in Fig. 4.…”
Section: Overall Process Of Gas Transport In Coalmentioning
confidence: 99%
“…Because it cannot be measured directly, there exists uncertainty in the values of tortuosity of nanoporous materials. Values between 1.5 and 8 have been reported by Wei et al (2007) and Busch et al (2008). If the kerogen porosity (the first parenthesis term on the right-hand side of Eq.…”
Section: Pore-scale Considerations In Organic-rich Gas Shalementioning
confidence: 99%
“…A dynamic multi-component transport (DMCT) model [22,23] was developed to deal with multi component gas counter-diffusionand flow in the coal matrix. Figure 6 shows the conceptual model.…”
Section: Research Backgroundmentioning
confidence: 99%